Development of West Greenlandic Markets for Country Foods Since the 18th Century - Marquardt, Ole; Caulfield, Richard A. (ARCTIC, 1996)
Local markets for country foods have a history in West Greenland dating back to the early 18th century. After Danish colonization in 1721, Greenlanders gradually began selling these foods (West Greenlandic: kalaalimerngit), which included seal, whale, caribou, fish, and birds - first to the Danes and later to other Greenlandic Inuit. This trade was a significant transformation of pre-contact Inuit exchange practices. In the 18th and early 19th centuries, the trade was largely between Greenlandic hunters and Danes employed by the colonial trade or by the church. Later in the 19th century, these institutions employed increasing numbers of indigenous Greenlanders. Economic specialization gradually became more pronounced within Greenlandic society, and cash became more prominent in local economies. Greenlandic hunters increasingly sold country foods to other Greenlanders earning wages. These practices continue today, with hunters regularly selling country foods in many towns at the local kalaalimineerniarfik (literally, "place where Greenlandic foods are sold"), to institutions such as schools or senior citizens' homes and in large stores. Today, Greenland's Home Rule government is promoting local country food markets as one strategy for sustainable development. The goals are to promote the use of nutritious and culturally valued foods on a sustainable basis and to provide economic opportunities for local hunters, particularly in outlying settlements. The history of Greenland's system for marketing country foods highlights some issues that may influence the contribution of country foods to sustainable community development in the Arctic. L'existence d'un marché régional des denrées tirées de la nature dans le Groenland occidental est attesté depuis le début du XVIIIe siècle. Après la colonisation danoise en 1721, les Groenlandais ont commencé à vendre graduellement ces produits alimentaires (kalaalimerngit, en Groenlandais occidental) - qui incluent phoque, baleine, renne, poisson et oiseaux - d'abord aux Danois, ...